O poema A esfinge de Emerson e a Conjectura ao enigma de Peirce - Louceiro, Luís Manuel Malta de Alves (2008)
The main objective of this Master s Dissertation is to know in an unprecedented work to what extent the mystic of Nature, orador, poet, essayist and Transcendentalist philosopher Ralph Waldo Emerson (1803-82) may have influenced Pragmaticist and Semiotician Charles Sanders Peirce (1839-1914) through his poem, The Sphynx (1841; translated for the first time into Portuguese in Annex 1), which stimulated the latter to offer an answer to the Emersonian enigma in the essay, A Guess at the Riddle (1887-88; translated for the first time into Portuguese in Annex 2), something that, later, according to Nathan Houser & Christian Kloesel, led to the construction of his admirable Architectonic (The Essential Peirce - Volume 1, 245), about which Peirce himself wrote: this book, if ever written, as it soon will be if I am in a situation to do it, will be one of the births of time (Ibid, ibidem). Therefore, in Part I we will analyze Emerson s poem and will highlight his Main Ideas, those present in his own books, essays and poems - before and after the making of the poem (1841) -, so we can know his intellectual development, in his rich dialog with the Western, Middle-Eastern and Eastern philosophies (that influenced him tremendously) -, once the key-idea behind this Master s Dissertation is grounded on Peirce s other comment on The Sphynx - symbols grow in the essay What Is A Sign? (1894) until we get to Emerson s Epistemology of Moods, his Existential Ethics of Sel-Improvement and his Metaphysics of Process, according to Stanley Cavell, who is responsible for the renaissance of Emerson s philosophical studies in the US in the last three decades. In Part II we will make a structural analysis (Martial Guéroult) of the answer Peirce gave to the Emersonian enigma in his essay, A Guess at the Riddle (1887-88)